Benefits of Stevia (Stevia rebaudiana B.) and Sirih (Piper betle L.) Leaves Combination Againts Dental Care - ilah karmila karmila (Sekolah Tinggi Ilmu Farmasi Yayasan Pharmasi Semarang, 2024)
Oral health is the most important part, to improve its hygiene by maintaining teeth. Cavities are a common problem. Betel leaf as an antibacterial. Stevia leaves as bacteriostatic and bactericidal also eliminate the cause of tooth decay and gingivitis. The purpose of the study was to determine the antibacterial activity of toothpaste combined with betel leaf extract with stevia leaves against the growth of Streptococcus mutans bacteria. The study used an experimental method consisting of making betel leaf and stevia leaf extracts using the maceration method. Preparation of toothpaste with a combination of betel leaf extract with stevia leaves at a concentration of 15% with the ratio of betel leaves and stevia leaves, namely formula 1 (5%: 10%), formula 2 (7.5%: 7.5%), formula 3 (10%: 5%). Testing antibacterial activity by measuring the clear zone using the disc paper method with blood agar media. Data analysis using ANOVA and Paired T test. The results of the study obtained formula (5%: 10%) clear zone of 16.42 mm, formula (7.5%: 7.5%) of 17.24mm, formula (10%: 5%) of 17.94mm, positive control of 18.66mm, negative control of 2.75mm. Conclusion 10:5 combination toothpaste has antibacterial activity.